Cloning and Characterization of Benzoate Catabolic Genes in the Gram-Positive Polychlorinated Biphenyl Degrader Rhodococcus sp. Strain RHA1 - Kitagawa, Wataru (American Society for Microbiology, 2001)
Benzoate catabolism is thought to play a key role in aerobic bacterial degradation of biphenyl and polychlorinated biphenyls (PCBs). Benzoate catabolic genes were cloned from a PCB degrader, Rhodococcus sp. strain RHA1, by using PCR amplification and temporal temperature gradient electrophoresis separation. A nucleotide sequence determination revealed that the deduced amino acid sequences encoded by the RHA1 benzoate catabolic genes, benABCDK, exhibit 33 to 65% identity with those of Acinetobacter sp. strain ADP1. The gene organization of the RHA1 benABCDK genes differs from that of ADP1. The RHA1 benABCDK region was localized on the chromosome, in contrast to the biphenyl catabolic genes, which are located on linear plasmids. Escherichia coli cells containing RHA1 benABCD transformed benzoate to catechol via 2-hydro-1,2-dihydroxybenzoate. They transformed neither 2- nor 4-chlorobenzoates but did transform 3-chlorobenzoate. The RHA1 benA gene was inactivated by insertion of a thiostrepton resistance gene. The resultant mutant strain, RBD169, neither grew on benzoate nor transformed benzoate, and it did not transform 3-chlorobenzoate. It did, however, exhibit diminished growth on biphenyl and growth repression in the presence of a high concentration of biphenyl (13 mM). These results indicate that the cloned benABCD genes could play an essential role not only in benzoate catabolism but also in biphenyl catabolism in RHA1. Six rhodococcal benzoate degraders were found to have homologs of RHA1 benABC. In contrast, two rhodococcal strains that cannot transform benzoate were found not to have RHA1 benABC homologs, suggesting that many Rhodococcus strains contain benzoate catabolic genes similar to RHA1 benABC.